Synthesis and characterization of multi-wall carbon nanotubes/DLC incorporated composites as electrode materials for supercapacitor - C. Suttichart (2020)
© 2019 Elsevier B.V. In this work, MWCNTs were synthesized by ACVD technique on the Cu substrate surface coated by DLC film prepared by radio frequency (RF) plasma treatment at the power of 50, 100 and 150 W in order to find the optimum conditions for MWCNTs to be utilized as an electrode material of a supercapacitor. Field Emission Scanning Electron Microscopy (FE-SEM) was employed in the characterization of the obtained MWCNTs. It was found that the MWCNTs grown on DLC film prepared at the plasma power of 100 W gave the highest percentage of carbon yield (188%), whereas the results from the Electrochemical Impedance Spectrometry (EIS) study showed that when used as an electrode of a supercapacitor, the MWCNT grown on DLC film prepared at the plasma power of 150 W yielded the highest parasitic capacitance of 421 μF/cm2.